Multi-Decadal Changes in Snow Characteristics in Sub-Arctic Sweden - Cecilia Johansson; Veijo A. Pohjola; Christer Jonasson; Terry V. Callaghan (AMBIO, 2011)
A unique long term, 49-year record (divided into three time periods 1961–1976, 1977–1992, and 1993–2009) of snow profile stratigraphy from the Swedish sub Arctic, was analyzed with a focus on changes in snow characteristics. The data set contained grain size, snow layer hardness, grain compactness, and snow layer dryness, observed every second week during the winter season. The results showed an increase in very hard snow layers, with harder snow in early winter and more moist snow during spring. There was a striking increase in the number of observations with very hard snow at ground level over time. More than twice as many occasions with hard snow at ground level were observed between 1993 and 2009 compared to previous years, which may have a significant effect on plants and animals. The changes in snow characteristics are most likely a result of the increasing temperatures during the start and the end of the snow season.